Greener neighbourhoods, slimmer children? Evidence from 4423 participants aged 6 to 13 years in the Longitudinal Study of Australian Children - Sanders, Taren; Astell-Burt, Thomas; Lonsdale, Chris; Fahey, Paul; Feng, Xiaoqi (My University, 2015)
Objective: There is a growing belief that green space (e.g. parks) help prevent obesity. There is evidence of an inverse association between green space and childhood body mass index (BMI); however, the majority of these studies are cross-sectional. Longitudinal studies which track change in BMI across childhood in relation to levels of green space proximity would improve the quality of evidence available for decision making. Methods: Objectively measured BMI was obtained every 2 years between 2006 and 2012 for 4423 participants initially aged 6-7 years in the Longitudinal Study of Australian Children (LSAC). The LSAC is a nationally representative study on a range of health and socio-demographic measures. Using Australian Bureau of Statistics mesh block data, which classify small scale land areas based on the main usage, each participant was assigned an objective measure of green space availability within their Statistical Area (level 2) of residence. Gender-stratified multilevel linear regression was used to estimate BMI growth curves across childhood in relation to green space availability. Family income, Australian Indigenous status, mothers’ education, and language spoken were used to adjust for socioeconomic confounding. Results: Age was found to be an effect modifier of associations between green space and BMI for boys (P=0.005) and girls (P=0.048). As children grew older, an inverse patterning of BMI by green space availability emerged. These findings held after adjustment for socioeconomic circumstances for boys (P=0.009), though were less robust for girls after this adjustment (P=0.056). Conclusion: A beneficial effect of green space on BMI emerges as children grow older. However, there was little additional benefit after a modest amount of green space was met. Further research is needed to understand if the drivers of this effect are from age-specific mechanisms, or whether the benefit of living in a greener neighbourhood is accumulated through childhood.
Keywords: Children -- Outcomes; Activities -- Outdoor activities; Health -- Body size, BMI, Body image; Health -- Obesity; Health and wellbeing; Childhood and child development; Activities; Health; Children; Obesity; Body size, BMI, Body image; Outdoor activities; Outcomes; Childhood and child development; Health and wellbeing